Measurements of the fast-ion distribution function at ASDEX upgrade by collective Thomson scattering (CTS) using active and passive views. (20th February 2015) - Nielsen, S K; Stejner, M; Rasmussen, J; Jacobsen, A S; Korsholm, S B; Leipold, F; Maraschek, M; Meo, F; Michelsen, P K; Moseev, D; Salewski, M; Schubert, M; et al.
Abstract: Collective Thomson scattering (CTS) can provide measurements of the confined fast-ion distribution function resolved in space, time and 1D velocity space. On ASDEX Upgrade, the measured spectra include an additional signal which previously has hampered data interpretation. A new set-up using two independent heterodyne receiver systems enables subtraction of the additional part from the total spectrum, revealing the resulting CTS spectrum. Here we present CTS measurements from the plasma centre obtained in L-mode and H-mode plasmas with and without neutral beam injection (NBI). For the first time, the measured spectra agree quantitatively with the synthetic spectra in periods with and without NBI heating. For the discharges investigated, the central velocity distribution of neutral beam ions can be described by classical slowing down. These results will have a major impact on ITER physics exploration, since CTS is presently the only diagnostic to measure the confined alpha particles produced by the fusion reactions.